Periodontoid Pseudotumor in Tuberous Sclerosis Associated With Neck Diffuse Lipomatosis - Pinto, E (2022)
Tuberous sclerosis (TS) is a genetic multisystem disorder associated with the development of benign tumors in many organs. Diffuse lipomatosis, which represents the overgrowth of fatty tissue in one part of the body, is a very rare finding reported in patients with tuberous sclerosis. We describe the case of a patient with diffuse lipomatosis in the right scapular, posterior cervical and perivertebral regions, associated with a space-occupying lesion adjacent to the odontoid process of C2 that appeared to be a pseudotumor, and discuss possible relation between these entities.